Emerging and Young Adulthood: Multiple Perspectives, Diverse Narratives - Konstam, Varda (Springer, 2015)
The most distinctive feature of the Second Edition is its theoretical orientation coupled with a focus on understanding emerging and young adulthood from multiple perspectives. The updated and expanded book offers readers an opportunity to “listen to the voices” of emerging and young adults, parents, and employers, which is key to understanding this particular developmental period. In addition, the case studies provided throughout the book are diverse and detailed.